Plastic wave propagation in Hopkinson bar - revisited - Mićunović, M.; Baltov, A. (Archives of Mechanics, 2002)
The subject of this paper is an analysis of the experimental Hopkinson bar technique when such a device consists of a short tensile or shearing specimen surrounded by two very long elastic bars [1]. Unlike the commonly applied by-pass analysis which attempts to draw conclusions from the behaviour of elastic bars, we attempt to take into account real plastic waves inside the specimen with several hundreds of reflections. A quasi rate-independent as well as a more general, rate-dependent tensor function model for AISI 316H calibrated in [19] are applied. Some special slightly perturbed elastic incident and reflected waves in elastic bars served to simulate the starting solutions. The numerical results have shown a good agreement with experimentally observed homogeneous strain state throughout the specimen during the process. Lindholm's procedure for finding specimen stress and strain by such a by-pass procedure is criticized.